2009
DOI: 10.1096/fj.09-138057
|View full text |Cite
|
Sign up to set email alerts
|

Signal transducer and activator of transcription 1 in T cells plays an indispensable role in immunity to Leishmania major by mediating Th1 cell homing to the site of infection

Abstract: The signal transducer and activator of transcription 1 (STAT1) signaling pathway mediates the biological functions of IFN-gamma. We have previously shown that the STAT1 pathway is indispensable for host resistance against Leishmania major infection. In this study, we examined the role of STAT1 in lymphocytes and specifically CD4(+) and CD8(+) T cells in mediating immunity against L. major by transferring T cells from wild-type (WT) and STAT1(-/-) C57BL/6 mice into Rag2(-/-) C57BL/6 mice. Rag2(-/-) mice reconst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Studies using STAT1 KO mice have implicated a role for STAT1 in both lymphocyte proliferation and migration (47)(48)(49). To address whether the absence of STAT1 affected the timing or magnitude of T cell infiltration into the infected brain parenchyma, immune cell profiles were determined in brain tissues of MV-infected NSE-CD46 + and NSE-CD46 + /STAT1-KO mice by flow cytometry and immunohistochemistry.…”
Section: T Cell Infiltration Into the Cns And Control And Clearance Omentioning
confidence: 99%
“…Studies using STAT1 KO mice have implicated a role for STAT1 in both lymphocyte proliferation and migration (47)(48)(49). To address whether the absence of STAT1 affected the timing or magnitude of T cell infiltration into the infected brain parenchyma, immune cell profiles were determined in brain tissues of MV-infected NSE-CD46 + and NSE-CD46 + /STAT1-KO mice by flow cytometry and immunohistochemistry.…”
Section: T Cell Infiltration Into the Cns And Control And Clearance Omentioning
confidence: 99%
“…However, the mechanism of inhibition of STAT1 by Leishmania may be even more complex as another study found that L. donovani, L. major and L. mexicana trigger the specific degradation of STAT1 by the proteasome; indeed, infection by the parasite was significantly inhibited by the addition of proteasome inhibitors to infected cells [213], raising the question of whether there can be specific targeting of STAT1a and not of STAT1b for the proteasome. The contribution of STAT1 to resistance to L. major appears to be an upregulation of CXCR3, which stimulates the migration of Th1 cells to the infection site [214]. In fact, another species, Leishmania amazonensis, was shown recently to efficiently downregulate the activation pathway of several cytokines, including IFNg, by inducing decreased phosphorylation of STAT1, STAT2 and STAT3 and also specific degradation of STAT2 [215]-an action that is prevented by proteasome inhibitors.…”
Section: Inhibition Of Stat1 Phosphorylationmentioning
confidence: 99%
“…62 In contrast, Barbi and colleagues demonstrated that STAT1 signaling in CD4 C T cells is essential for the development of an antimicrobial state against L. major, whereas it is not essential in CD8 C T cells. 63 Additional results have suggested that STAT1 expression is critical for preventing systemic dissemination of parasite infection, most probably by controlling the migration of Th1 cells to sites of inflammation rather than their generation. 63 …”
Section: Lessons Learned From Other Kinetoplastidsmentioning
confidence: 99%
“…63 Additional results have suggested that STAT1 expression is critical for preventing systemic dissemination of parasite infection, most probably by controlling the migration of Th1 cells to sites of inflammation rather than their generation. 63 …”
Section: Lessons Learned From Other Kinetoplastidsmentioning
confidence: 99%